PENGARUH GAYA MENGAJAR GURU TERHADAP KECERDASAN VISUAL-SPASIAL SISWA KELAS IV SD KHADIJAH SURABAYA - Ulvi Nur Laily; Nafiah Nafiah; Sri Hartatik; Mohammad Taufiq (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is about the effect of teacher teaching style on visual-spatial intelligence of fourth grade students of Khadijah Surabaya Elementary School. The purpose of this researh was to determine the teaching style used by fourth grade teachers, to determine the visual-spatial intelligence of fourth grade students, and to determine the effect of the teacher's teaching style on the visual-spatial intelligence of fourth grade students. The research method used was quantitative research, the type of correlational research. The total population in this study was 123 students with a total sample of 95 students. Data collection techniques used was a questionnaire with the number of questions 23 variable X questions and 15 valid variable Y questions with a reliable value of 0.893 (variable X) and 0.783 (variable Y). Data analysis techniques used was the Pearson product moment test. The results of this study indicated that: 1) the teaching style used by fourth grade teachers was classical 31.58%, technologically 38.95%, personalization 7.37%, and interactional 22.1%, 2) visual-spatial intelligence of 72 fourth grade students (75.8%) were in the high category, 22 students (23.2%) were in the medium category, and 1 student (1.1%) was in the low category, 3) The teaching style of the teacher had moderate influence on visual-spatial intelligence of fourth grade students with a correlation coefficient of 0.521 and a significance value of 0.000 <0.01. This research hopes to shed some light for researchers, teachers, and schools to apply teaching styles that are in accordance with students' visual-spatial intelligence.